Applying genesis model in researching Nha Trang coastline evolution :Master thesis Major Coastal Engineering and Management: Code 62-58-02-03 - Vũ, Duy Toàn (Trường Đại học Thủy Lợi, 2020)
This Master programme is supported by NICHE - VNM 106 Project